(untitled) (Fiep Bulletin - online, 2011)
The National Curriculum Guidelines for Undergraduate Physiotherapy guide and orient the development of the education program which shall include the specifics of current reality, among them the elderly. Gerontology as an area of knowledge, provides grants to these professionals for the debunking of old age through the scientific interpretation of the facts, answering many questions pertaining to the longevity and aging, resulting from the transformation process we go through. In this sense, our goal is to identify and analyze the curriculum practices relating to the human aging process and health of the elderly of the Physiotherapy Course at the University of Western Paraná / UNIOESTE in order to contribute to the evaluation and revision of training programs such professionals, so they are better motivated and prepared to carry out their work with the elderly. This research is qualitative, the data were obtained through document analysis and content analysis, having as main source of Project Political Course of Physiotherapy UNIOESTE. They were analyzed through detection of words that deal with the theme aging. After collating the data, we confront the theory with the study. We conclude that the courses of therapy include, in general, the subjects with programming designed to study the issues involving the elderly. However, further studies should look if this approach is restricted to health approach.